Development of Ga-68-labelled ultrasound microbubbles for whole-body PET imaging - Hernandez-Gil,J; Braga,M; Harriss,B; Carroll,LS; Leow,CH; Tang,M-X; Aboagye,EO; Long,NJ (Chemical Science, 2019)
Microbubble (MB) contrast agents have revolutionalised the way ultrasound (US) imaging can be used clinically and pre-clinically. Contrast-enhanced US offers improvements in soft-tissue contrast, as well as the ability to visualise disease processes at the molecular level. However, its inability to provide in vivo whole-body imaging can hamper the development of new MB formulations. Herein, we describe a fast and efficient method for achieving 68Ga-labelling of MBs after a direct comparison of two different strategies. The optimised approach produces 68Ga-labelled MBs in good yields through the bioorthogonal inverse-electron-demand Diel–Alder reaction between a trans-cyclooctene-modified phospholipid and a new tetrazine-bearing HBED-CC chelator. The ability to noninvasively study the whole-body distribution of 68Ga-labelled MBs was demonstrated in vivo using positron emission tomography (PET). This method could be broadly applicable to other phospholipid-based formulations, providing accessible solutions for in vivo tracking of MBs.